2009
DOI: 10.1111/j.1365-2923.2009.03371.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and medical specialty choice: findings from three empirical studies

Abstract: Across all three studies - and using both classifications of specialty choice - no significant differences in EI were found between students entering primary care and non-primary care specialties. Limitations are acknowledged, and future directions for research involving EI are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 25 publications
1
41
0
1
Order By: Relevance
“…Previously conducted studies suggest a relationship between: (1) empathetic concern (Interpersonal Reactivity Index) measured at the end of clerkship training and residency specialty area (Borges et al 2009); (2) changes in vicarious empathy scores (Balanced Emotional Empathy Scale) during medical school and residency specialty area (Newton et al 2008); (3) vicarious empathy scores (Balanced Emotional Empathy Scale) and medical students' specialty intentions; and finally, (4) empathy scores (Jefferson Scale of Physician Empathy) and physicians' specialty areas (Newton et al 2000;Hojat et al 2002). Although empathy is a multi-dimensional construct likely to be among the complex array of factors that have a role in specialty choice decision making, our finding of stability of specialty preference for nearly threefourth of students and no predictive relationship between empathy scores at baseline or changes in empathy scores and changes in specialty preference suggests that the decline in empathy experienced all too often by medical students during training is not having a major role in shaping students' specialty preference or interest in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Previously conducted studies suggest a relationship between: (1) empathetic concern (Interpersonal Reactivity Index) measured at the end of clerkship training and residency specialty area (Borges et al 2009); (2) changes in vicarious empathy scores (Balanced Emotional Empathy Scale) during medical school and residency specialty area (Newton et al 2008); (3) vicarious empathy scores (Balanced Emotional Empathy Scale) and medical students' specialty intentions; and finally, (4) empathy scores (Jefferson Scale of Physician Empathy) and physicians' specialty areas (Newton et al 2000;Hojat et al 2002). Although empathy is a multi-dimensional construct likely to be among the complex array of factors that have a role in specialty choice decision making, our finding of stability of specialty preference for nearly threefourth of students and no predictive relationship between empathy scores at baseline or changes in empathy scores and changes in specialty preference suggests that the decline in empathy experienced all too often by medical students during training is not having a major role in shaping students' specialty preference or interest in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…127 Our review identified 5 studies that commented on how prestige and financial reward factored into career decisions among medical students. 96,[128][129][130][131] These studies reported that medical students who valued prestige, financial gain and academic ambition tended to pursue careers in surgery more frequently than their counterparts, suggesting a personality that is more drawn to surgery.…”
Section: Personality Typementioning
confidence: 99%
“…Several reviews have highlighted the loose definition of EI, which on the one hand, appears to be trainable, so not a form of intelligence, and on the other, appears to be strongly related to personality, which then suggests it is not a measure of aptitude (Lewis et al 2005;Romanelli et al 2006;Davies et al 1998). EI, after all is said and done, appears unrelated to career choice (Borges et al 2009), academic performance (Romanelli et al 2006;Newsome et al 2000) or doctor-patient relationship (Weng et al 2008). It remains to be shown if it has any value in health sciences education.…”
Section: Multiple Intelligences Practical Intelligence and Emotionalmentioning
confidence: 99%